Epidemiologia da Alternariose e resistência de cultivares em brássicas sob diferentes sistemas de cultivo - RODRIGUES, Viviane Jurema Lopes Borges (2003)
Cabbage (Brassica oleracea var. capitata ), cauliflower (Brassica oleracea var. botrytis), Chinese cabbage (Brassica pekinnensis) and broccoli (Brassica oleracea var. italica) have high economic expression in the Agreste region in the State of Pernambuco, Brazil. However, the occurrence of foliar diseases such as Alternaria black spot, caused by Alternaria brassicicola, represent great worry in farming systems areas. Thus, this research aimed to analyze the epidemiology of Alternaria black spot on Taibyo cultivar of Chinese cabbage in different farming systems (conventional, organic and protected); at four transplant seasons and two irrigation systems under organic farming; at three transplant spacing under conventional farming; as well as analyze the comparative epidemiology of Alternaria black spot in 22 brassica cultivars being nine broccoli, five Chinese cabbage, four cauliflower andfour cabbage, under conventional and organic farming systems. Evaluations of the beginning of initial symptoms (BIS) and severity of the disease on every leaf of 10 plants were made. Disease progress curves were ploted, and epidemiology were compared through by BIS, maximum disease severity (ymax), disease progress rate (DPR), and the area under disease progress curves (AUDPC) in all experiments. The October 2000 transplant season was the most propitious to Alternaria black spot, while the July 2001 transplant season was unfavorable to disease development, since it took longer for the symptoms to show, and the values of ymax and DPR were lower than in other periods. Comparing the three farming systems, the highest values of ymax, DPR and AUDPC were observed in organic farming, indicating that this condition was the most favorable to Alternaria black spot. Trickle irrigation compared to the sprinkle system showed lower development of Alternaria blackspot, represented by lower values of ymax, DPR and AUDPC. As far as spacing is concerned, the combination 0.33 x 0.50 m showed the lowest values of ymax and AUDPC. All brassicacultivars evaluated were susceptible to A. brassicicola. In most situations, significative difference was detected among cultivars grown in the same farming system. Higher disease intensity was obeserved in organic farming system. Chinese cabbage (Tropical Pride and Tropical Delight), cauliflower (Arfak), and cabbage (Fuyutoyo and Rubro) had the lowest disease levels. . On all situations, significative correlations were noted among the severity of Alternaria black spot disease and both the highest temperature average and the relative air humidity in the 14 days prior to the disease evaluation.